PENERAPAN MODEL PEMBELAJARAN JIGSAW PADA MATERI CAHAYA DAN ALAT OPTIK - Nur Choridatul Fitri; Nur Kuswanti; Lina Arifah Fitriyah (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2019)
The general purpose of this study was to describe the application of the jigsaw learning model on Light and Optical Devices material. The specific purposes were (1) describing the implication of the jigsaw learning model, (2) describing completeness of learning after applying the jigsaw learning model and (3) describing student responses after learning by applying the jigsaw learning model. This was a quantitative and qualitative descriptive research because the data obtained was the form of the nominal described. Data collection techniques in the study were observation, test and questionnaires methods. The data gained were analysed used qualitative and quantitative fly The results showed that The implementation of learning based on teacher activities at the first and second meetings goes an average of 82,35% with very good criteria. The value of completeness of students achieved 86 with complete criteria. Students’ positive response to model jigsaw learning reached 90,95% with very good criteria.